2018
DOI: 10.1080/01441647.2018.1494640
|View full text |Cite
|
Sign up to set email alerts
|

Governing autonomous vehicles: emerging responses for safety, liability, privacy, cybersecurity, and industry risks

Abstract: The benefits of autonomous vehicles (AVs) are widely acknowledged, but there are concerns about the extent of these benefits and AV risks and unintended consequences. In this article, we first examine AVs and different categories of the technological risks associated with them. We then explore strategies that can be adopted to address these risks, and explore emerging responses by governments for addressing AV risks. Our analyses reveal that, thus far, governments have in most instances avoided stringent measu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
209
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 412 publications
(219 citation statements)
references
References 41 publications
1
209
0
9
Order By: Relevance
“…More research is required to address the high costs and low scalability of many system verification tools for AVs. It is also important to supplement these verification tools with adaptive policies and regulation that involves knowledge generation through investigative programmes, reviewing that knowledge such as through safety review boards and altering safety requirements in tandem with technological developments [41,145]. Other technical issues include the detection of inevitable sensor failures and cybersecurity risks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More research is required to address the high costs and low scalability of many system verification tools for AVs. It is also important to supplement these verification tools with adaptive policies and regulation that involves knowledge generation through investigative programmes, reviewing that knowledge such as through safety review boards and altering safety requirements in tandem with technological developments [41,145]. Other technical issues include the detection of inevitable sensor failures and cybersecurity risks.…”
Section: Discussionmentioning
confidence: 99%
“…At Level 3 (conditional automation), the vehicle can perform all dynamic driving Sustainability 2019, 11, 5791 3 of 28 tasks such as steering, acceleration, and monitoring the environment, but the human driver is required to resume control occasionally [39,40]. Vehicles classified under Levels 4 and 5 of autonomy are considered highly and fully autonomous respectively as they can engage in all the driving tasks without human intervention [41].…”
Section: Avsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, an increase in either of them can be driven by, as well as result in, an increase in the other. Recently, US governments have enacted a new legislation known as the SPY Car Act on data privacy that provides jurisdiction to the NHTSA to protect the use of driving data in all vehicles manufactured for sale in the US (Taeihagh and Lim, 2019). This is likely to favour customers" acceptance of AVs.…”
Section: Cld: Feedback Loopsmentioning
confidence: 99%
“…Recently, a few researchers have argued that a wider range of user concerns should be researched Taeihagh and Lim 2018). have conducted a stakeholder workshop, which showed that stakeholders in the UK worry about additional aspects of AVs than those addressed in autonomous car innovation trajectories, e.g., cyber security, data ownership, sustainability, energy use and air quality, equity and access.…”
Section: User Attitudes Of Autonomous Vehiclesmentioning
confidence: 99%